2015
DOI: 10.1186/s12866-015-0495-4
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activities of actinomycetes isolated from unexplored regions of Sundarbans mangrove ecosystem

Abstract: BackgroundNew broad spectrum antimicrobial agents are urgently needed to combat frequently emerging multi drug resistant pathogens. Actinomycetes, the most talented group of microorganisms isolated from unexplored regions of the world may be the ultimate solution to this problem. Thus the aim of this study was to isolate several bioactive actinomycetes strains capable of producing antimicrobial secondary metabolite from Sundarbans, the only mangrove tiger land of the world.ResultsFifty four actinomycetes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(75 citation statements)
references
References 58 publications
4
68
1
2
Order By: Relevance
“…In isolating actinomycetes, soil samples are collected from the study area [16][17][18][19][20]. To kill most of the Gram negative bacteria, the soil is dried on the bench inside the laboratory for a period of one week [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In isolating actinomycetes, soil samples are collected from the study area [16][17][18][19][20]. To kill most of the Gram negative bacteria, the soil is dried on the bench inside the laboratory for a period of one week [17].…”
Section: Introductionmentioning
confidence: 99%
“…To kill most of the Gram negative bacteria, the soil is dried on the bench inside the laboratory for a period of one week [17]. The soil is further held in a water bath at 50°C to further destroy other vegetative microorganisms [13].…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of the media plays a significant role in the expression of genes of the metabolic pathways, and thereby production of maximum antimicrobial compounds (Sengupta et al 2015). In the current study, crude extract prepared from King's B media was found to exhibit highest inhibition against the selected test organisms (Table 3).…”
Section: Media Optimization For Bioactive Compound Productionmentioning
confidence: 99%
“…100 L from 10 -2 dilution was spread on starch casein nitrate agar (composition in media g/L: starch 10, casein 0.3, KNO3 5, NaCl2 2, K2HPO4 2, MgSO4.7H2O 0.5, CaCO3 0.02, FeSO4.7H2O 0.01 and agar 18; pH was adjusted to 7 ± 0.2) (Sengupta et al, 2015), glycerol casein agar (Kuster agar) (composition in media g/L: glycerol 10, casein 0.3, KNO3 2, K2HPO4 2, MgSO4 0.05, CaCO3 0.02, Fe2 (SO4)3.6H2O 0.01, Agar 15 and pH was adjusted to 7 ± 0.2 ) (Lakshmanaperumalsamy et al, 1984) and yeast extract starch casein agar (YSCA) (composition in media g/L: yeast extract 3, peptone 3, casein 3, starch 8, K2HPO4 0.5, MgSO4.7H2O 0.5, NaCl 2, agar 15 and pH 7.0 to 7.6 ) (Mincer et al, 2002). The inoculated plates were incubated at 28°C for 7 to 14 days.…”
Section: Isolation Of Actinomycetesmentioning
confidence: 99%